Feminist Critique of Joseph Stiglitz’s Approach to the Problems of Global Capitalism - Blake, Jenna (Stance: an international undergraduate philosophy journal, 2014)
In his book Making Globalization Work, Joseph Stiglitz proposes reforms to address problems arising from the global spread of capitalism, problems that he asserts are not inherent to globalization or capitalism but are due to the way those systems have been “managed.” Conversely, postcolonial feminist theorist Chanda Talpade Mohanty’s analysis of those same systems demonstrates that capitalism is not compatible with global justice. In this essay I use Mohanty’s analysis to argue that Stiglitz’s proposed reforms would not achieve his stated goals and that the global capitalist system must be dismantled if global justice is to be achieved.